Portrayal of Women's Leadership in Wajah Seorang Wanita from the Management Approach Perspective: (Potret Kepimpinan Wanita dalam Wajah Seorang Wanita dari Perspektif Pendekatan Pengurusan) (Malay Literature, 2020)
Women have many advantages and important roles in the family institution. Nowadays, many women are involved in various professions including entrepreneurship, corporate positions and leadership. Therefore, this article aims to analyse the fundamentals of women's leadership as the head and manager of the family-roles traditionally reserved for men. This study applies the principles of leadership in the Management Approach on S. Othman Kelantan's novel, Wajah Seorang Wanita. Library research and qualitative methods were applied in this study. The analysis shows that three out of the four dimensions of leadership principles apply, namely, the administrative, economic and educational dimensions. This is depicted through the novel's main character, Siti Musalmah, who has to manage and lead her family after the death of her beloved husband. This study also seeks to unveil the role of women and thus elevate the status of women as heads of families despite having to face great challenges as single mothers. As a result, the Management Approach, using principles of leadership, allows a clarification and analysis of the principles of management practiced by women in caring for the well-being of their familis. Wajah Seorang Wanita is a portrayal of the leadership of a woman during the time of the Japanese Occupation.Keywords: characteristics, portrayal, educational dimensions, administrative dimensions, economic dimensions